A new genus and species of club-horned wasps, with a key to the Old World genera of Sapyginae (Hymenoptera, Sapygidae) - Loon, Milo Van (Zootaxa, 2024)
A new genus and species of the family Sapygidae from Southeast Asia is described: Dasysapyga picta van Loon, gen. et sp. nov. The new genus is similar to Parasapyga Turner, 1910, but differs mainly in sculpture, wing venation and pubescence. A key to the Old World genera of the subfamily Sapyginae is provided.